Pengaruh Pelatihan, Gaya Kepemimpinan, Dan Beban Kerja Terhadap Produktivitas Kerja Karyawan - Oktaviani, Alia (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
In today's business world, competition is fierce, thus businesses are expected to be able to adapt to changing market conditions in a practical and swift manner. As a result, businesses should be able to meet set goals. The ability of an organisation to fulfil its mission and vision is evaluated by the SDM. This analysis's goal is to identify training effectiveness, employee morale, and work-related stress in relation to employees' job productivity. This analysis is a review of the literature that highlights recent research findings. The study's findings on the training variable and leadership style indicate that there is a positive correlation with employee productivity. The work-related variable bears a negative correlation with employee productivity. The constant work environment reduces the productivity of employees in their jobs.